Modeling social interaction and metapopulation mobility of the COVID-19 pandemic in main cities of highly populated Java Island, Indonesia: An agent-based modeling approach - Ahmad, Riris Andono; Imron, Muhammad Ali; Ramadona, Aditya Lia; Lathifah, Nurul; Azzahra, Faradhina; Widyastuti, Kirana; Fuad, Anis (Frontiers in Ecology and Evolution, 2023)
Coronavirus transmission is strongly influenced by human mobilities and interactions within and between different geographical regions. Human mobility within and between cities is motivated by several factors, including employment, cultural-driven, holidays, and daily routines. We developed a Sustained Metapopulation (SAMPAN) model, an agent-based model (ABM) for simulating the effect of individual mobility and interaction behavior on the spreading of COVID-19 viruses across main cities on Java Island, Indonesia. The model considers social classes and social mixing affecting the mobility and interaction behavior within a sub-population of a city in the early pandemic. Travelers' behavior represents the mobility among cities from central cities to other cities and commuting behavior from the surrounding area of each city. Local sensitivity analysis using One factor at a time was performed to test the SAMPAN model, and we have identified critical parameters for the model. While validation was carried out for the Jakarta area, we are confident in implementing the model for a larger area with the concept of metapopulation dynamics. We included area of Bogor, Depok, Bekasi, Bandung, Semarang, Surakarta, Yogyakarta, Surabaya and Malang cities which have important roles of pandemic COVID-19 spreading in this island. Our SAMPAN model can simulate various waves during the first year of the pandemic, caused by various phenomena of large social mobilities and interactions, particularly during religious occasions and long holidays.